2016
DOI: 10.1016/j.agwat.2016.10.011
|View full text |Cite
|
Sign up to set email alerts
|

A synthesis and comparative evaluation of factors influencing the effectiveness of drainage water management

Abstract: Viable large-scale crop production in the United States requires artificial drainage in humid and poorly drained agricultural regions. Excess water removal is generally achieved by installing tile drains that export water to open ditches that eventually flow into streams. Drainage water management (DWM) is a conservation practice that allows farmers to artificially raise the outlet elevation of a field's drain tile and can reduce nutrient loss during wet periods by storing more water in the field. We intended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 48 publications
5
32
1
Order By: Relevance
“…The impact of CD on P concentrations in drain water has not been as widely studied as the impact on N according to a recent review by Ross et al (2016). A concern related to CD is that the elevation of the groundwater level will create conditions sufficiently reduced for Al‐ or Fe‐bound PO 4 3− to be released when mineral oxides are reduced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of CD on P concentrations in drain water has not been as widely studied as the impact on N according to a recent review by Ross et al (2016). A concern related to CD is that the elevation of the groundwater level will create conditions sufficiently reduced for Al‐ or Fe‐bound PO 4 3− to be released when mineral oxides are reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Another less intensively studied aspect of CD is the effect on P (Ross et al, 2016), and studies have shown promising results with P retention from 40 to 95% compared with conventional drainage levels. However, it is a concern that CD might increase dissolved PO 4 3− loss as reduced conditions can lead to PO 4 3− desorption from hydrous iron oxides if Fe 3+ is reduced to Fe 2+ (Kadlec and Wallac, 1996).…”
Section: Controlled Drainage As a Targeted Mitigation Measure For Nitmentioning
confidence: 99%
“…However, for fields with elevated STP (>75 to 80 ppm M3P), attainment of water quality goals may only be addressed through other measures or a combination of practices including drawdown (Withers et al, 2014; Rowe et al, 2016) or a one‐time inversion tillage if severely stratified to increase the buffering capacity of the upper layers of the soil (Sharpley, 2003; Baker et al, 2017). In addition to drawing down STP or implementing inversion tillage, gypsum (Chardon et al, 2012; King et al, 2016) and controlled drainage (Williams et al, 2015a; Ross et al, 2016) offer alternative practices to potentially remove or mitigate P loss.…”
Section: Discussionmentioning
confidence: 99%
“…However, this is not always feasible in urban settings, and therefore use of a slow-release P fertilizer is warranted. Last, reduction of runoff and sub-surface drainage volumes in agricultural settings can be achieved through practices such as tile drain flow-control structures and vegetated buffer strips [4,5]. These practices are mostly incompatible with urban watersheds, which are usually highly impermeable and with runoff as the predominant source of water.…”
Section: Purpose and Justification For Phosphorus Removal Structuresmentioning
confidence: 99%